Factors influencing the effectiveness of surgical therapy of peri‐implantitis - Ausra Ramanauskaite; Wenije Zhou; Emilio A. Cafferata; Frank Schwarz (Periodontology 2000, 2026)
Abstract Background Surgical therapy is required in the majority of peri‐implantitis cases due to the inconsistent efficacy of non‐surgical approaches. Although surgical treatment generally offers higher predictability, reported success rates vary widely. Aim To review the available evidence on the factors influencing the outcomes of peri‐implantitis surgical therapy, including surgical technique, implant‐site characteristics, and patient‐related conditions. Materials and Methods This narrative review is based on a literature search conducted in three electronic databases to identify relevant studies published between January 2010 and November 2025. Results Surgical factors: The adjunctive use of reconstructive measures improves radiographic defect fill and may help maintain soft‐tissue levels, although no clear benefits have been demonstrated in the resolution of clinical signs of inflammation compared with non‐reconstructive approaches. Contained intrabony defects (3‐ and 4‐wall) consistently demonstrate more favorable outcomes of reconstructive therapy compared with non‐contained defects (1‐ and 2‐wall). Reconstruction protocols that incorporate slowly resorbing bone substitutes may lead to more favorable outcomes compared with autogenous bone. No definitive conclusions could be made regarding the optimal flap design, postoperative healing mode (i.e., submerged versus non‐submerged), or the benefits of adjunctive membranes, systemic antibiotics, or additional use of biologics. Overall, the effectiveness of surgical peri‐implantitis treatment is associated with the surgeon's level of experience. Implant‐site‐related factors: Initial disease severity characterized by extensive bone loss, suppuration, deep probing depths, rough implant surfaces, and persistent bleeding after surgery have been identified as major factors compromising treatment success. Conversely, the presence of keratinized mucosa appears to enhance the outcomes of reconstructive peri‐implantitis therapy. Emerging evidence points to an association between macrophage polarization and the outcomes of surgical peri‐implantitis treatment. Patient‐related factors: Current evidence underscores the essential role of patient adherence to supportive postoperative care in maintaining the results achieved surgically. Findings concerning the influence of a history of periodontitis, smoking status, and gender remain inconsistent. Conclusions Outcomes of surgical peri‐implantitis treatment are determined by a complex interplay of defect morphology, disease severity, implant surface characteristics, surgical expertise, and patient adherence to supportive care. Clinical Relevance Clinically, careful case selection, defect‐specific surgical planning, and strict postoperative maintenance are essential to enhance predictability and long‐term stability.